Effect of Short-Term Use of Anti-Pronation Insoles on Plantar Pressure Variables Following Anterior Cruciate Ligament Reconstruction with a Pronated Foot during Gait - Raziyeh Alizadeh; Amir Ali Jafarnezhadgero; Davood Khezri; Heidar Sajedi; Ehsan Fakhri Mirzanag (مجله دانشگاه علوم پزشکی گرگان, 2024)
Background and Objective: Individuals with a history of anterior cruciate ligament (ACL) injury are at a higher risk of re-injury compared to healthy individuals. ACL-injured patients exhibit weaker longitudinal arches and increased foot pronation compared to healthy individuals. This study aimed to determine the effect of short-term use of anti-pronation insoles on plantar pressure variables following ACL reconstruction (ACLR) with a pronated foot during gait. Methods: This quasi-experimental study was conducted on 15 male participants who had undergone ACLR with a pronated foot (mean age= 23.2±4.5 years) and 15 healthy males (mean age= 22.7±4.3 years) in Ardabil, Iran during 2022. Plantar pressure values during gait with and without the use of anti-pronation insoles were recorded and compared using a foot scanner (sampling rate: 300 Hz). Results: The effect of the group factor on the big toe plantar pressure variable was statistically significant (P<0.05). Pairwise comparison results demonstrated a significant increase in pressure in the ACLR group (154.63±41.71 N/cm²) compared to the healthy group (126.54±26.57 N/cm²) (P<0.05). Intragroup comparison results revealed a significant decrease in pressure on the second to fifth toes (215.73±60.74 N/cm²) and the first plantar (420.58±107.56 N/cm²) when using anti-pronation insoles compared to the non-insole condition (the second to fifth toes (201.57±76.21 N/cm²) and the first plantar (400.78±118.20 N/cm²) in the ACL reconstruction group (P<0.05). Conclusion: The use of anti-pronation insoles can effectively reduce plantar pressure after ACLR in individuals with a pronated foot during gait.